2017
DOI: 10.1097/ans.0000000000000163
|View full text |Cite
|
Sign up to set email alerts
|

Embedding a Palliative Approach in Nursing Care Delivery

Abstract: A palliative approach involves adapting and integrating principles and values from palliative care into the care of persons who have life-limiting conditions throughout their illness trajectories. The aim of this research was to determine what approaches to nursing care delivery support the integration of a palliative approach in hospital, residential, and home care settings. The findings substantiate the importance of embedding the values and tenets of a palliative approach into nursing care delivery, the rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 64 publications
0
47
0
Order By: Relevance
“…Genuine presence and partnership in setting goals of care can help people with life‐threatening illnesses and their family members navigate the difficult existential questions relating to living and dying. Creating space for conversation about EOL also aligns with values inherent in a palliative approach (Sawatzky et al., ) and holistic care (Noble, Brown, Shields, Fogarty, & Maxwell, ).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Genuine presence and partnership in setting goals of care can help people with life‐threatening illnesses and their family members navigate the difficult existential questions relating to living and dying. Creating space for conversation about EOL also aligns with values inherent in a palliative approach (Sawatzky et al., ) and holistic care (Noble, Brown, Shields, Fogarty, & Maxwell, ).…”
Section: Discussionmentioning
confidence: 92%
“…Palliative care is an approach that focuses on improving “the quality of life of people and their families facing the problem associated with life‐threatening illness, through the prevention and relief of suffering by means of early identification and impeccable assessment and treatment of pain and other problems, physical, psychosocial, and spiritual” (WHO, ). A palliative approach, that uses “principles of palliative care [that] are adapted and integrated into contexts of care that do not give specialized palliative care services, regardless of the healthcare sector where the service is provided” (Sawatzky et al., , p. 1), seems particularly appropriate given the organization of renal care services. “Supportive care” is a term recently used in the literature relating to EOL with CKD that offers language that is preferred by people and health professionals in this setting (Davison et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research examining staff perspectives of their involvement in end-of-life decision-making has indicated that LTC home staff tends to be excluded, and exclude themselves, from decision-making. Studies have found that nurses perceive a lack of power and knowledge and are ambiguous regarding their role related to endof-life conversations (Laging, Ford, Bauer, & Nay, 2015;Lopez, 2007Lopez, , 2009Reimer-Kirkham, Sawatzky, Roberts, Cochrane, & Stajduhar, 2016;Sawatzky et al, 2017). Nurses have characterized their role as playing the middle person between family members and physicians (Bryon, Gastmans, & de Casterle, 2008;Lopez, 2007Lopez, , 2009.…”
Section: End-of-life Decision-making For People With Dementiamentioning
confidence: 99%
“…In recent years, several programs or strategies have been developed within longterm care (LTC) contexts to improve the delivery of a palliative approach to care and build capacity to support sustainable change (Hockley and Froggatt 2006;Kaasalainen et al 2019;Palliative Alliance 2017;Parker et al 2010). As defined by Sawatzky et al (2016Sawatzky et al ( , 2017, a palliative approach to care consists of an upstream orientation toward the needs of people living with life-limiting conditions and their families, adaptation of palliative care knowledge and expertise and operationalization of a palliative approach through integration into systems and models of care that do not specialize in palliative care. Importantly, a focus on advance care planning (ACP) helps to ensure early discussions about wishes and values that will contribute to goals of care and treatment decisions at end of life.…”
Section: Introductionmentioning
confidence: 99%